Style-shifting in Usage Instructions of Food, Beverage, and Pharmaceutical Products in Japanese Language - Mulyadi Mulyadi; Suhandano Suhandano; Aris Munandar (Japanese Research on Linguistics, Literature, and Culture, 2021)
The present article attempts to describe the shifting use of formal and informal styles in usage instruction discourse of food, beverage, and pharmaceutical products in Japanese. The aim is to explain the background of style-shifting from a formal style, indicated by -desu in adjectives and nouns and -masu in verbs, into an informal style without any -desu or –masu forms in place. The background is reviewed through the perspectives of both sociolinguistics and pragmatics. The data were collected from various food, beverage, and pharmaceutical product packages containing usage instructions in Japanese. Study results indicate that style-shifting does not only occur through spoken language (orally) but via written discourse, which maintains unchanging external factors or definite contexts. Style-shifting is not only affected by the status of the speech partner but also more likely affected by the content of the information delivered to the consumers. Aside from occurring within a single discourse, style-shifting is also observed at a narrower level, namely within one element of discourse conveying a relatively homogenous information.